Phase II study on early start of chemotherapy after excising primary colorectal cancer with distant metastases (Pearl Star 02). Issue 3 (14th August 2017) - Yoshida, Yoichiro; Aisu, Naoya; Kojima, Daibo; Mera, Toshiyuki; Kiyomi, Fumiaki; Yamashita, Yuichi; Hasegawa, Suguru
Abstract: Initiating chemotherapy usually requires a delay of more than 4 weeks after surgically resecting colorectal cancer. However, there is little evidence regarding the required delay interval. We have previously reported a pilot study to determine the safety and feasibility of early initiation of chemotherapy after resecting primary colorectal cancer with distant metastases. We aimed to determine the safety and efficacy of early initiation of chemotherapy after resecting colorectal cancer with distant metastases. This phase II study (trial number UMIN000006310) was a prospective, single‐arm trial. A total of 20 patients (men, 15 and women, 5) were enrolled. They underwent XELOX therapy (130 mg/m 2 oxaliplatin on day 1+1000 mg/m 2 capecitabine twice daily on days 1‐4) on postoperative day 7 and XELOX+bevacizumab (7.5 mg/kg bevacizumab on day 1) after the second chemotherapy cycle. Baseline characteristics included a median age of 64 (range, 43‐72) years. Surgical procedures included right hemicolectomy in six patients, sigmoidectomy in three, anterior resection in five, and Hartmann procedure in six. All patients started chemotherapy on postoperative day 7. Median progression‐free survival was 14.9 months; overall response rate was 80%. Disease control rate was 100%. Grade 3 or higher hemotoxicity and grade 3 or higher non‐hematological toxicity was noted in 5.0% and 25.0% of patients, respectively. Postoperative complications were observed in two patients (superficial incisional surgical site infection and ileus). Early initiation of chemotherapy after surgery is feasible. These findings suggest future changes of the start time of chemotherapy after surgery. Abstract : Starting chemotherapy usually requires a delay of more than 4 weeks after surgically resecting colorectal cancer. However, there is little evidence regarding the required delay interval. We aimed to determine the safety and efficacy of early initiation of chemotherapy after resecting colorectal cancer with distant metastases.